Radical SAM Enzymes in the Biosynthesis of Ribosomally Synthesized and Post-translationally Modified Peptides (RiPPs) - Benjdia, Alhosna; Balty, Clémence; Berteau, Olivier (Frontiers in Chemistry, 2017)
Ribosomally-synthesized and post-translationally modified peptides (RiPPs) are a large and diverse family of natural products. They possess interesting biological properties such as antibiotic or anticancer activities, making them attractive for therapeutic applications. In contrast to polyketides and non-ribosomal peptides, RiPPs derive from ribosomal peptides and are post-translationally modified by diverse enzyme families. Among them, the emerging superfamily of radical SAM enzymes has been shown to play a major role. These enzymes catalyze the formation of a wide range of post-translational modifications some of them having no counterparts in living systems or synthetic chemistry. The investigation of radical SAM enzymes has not only illuminated unprecedented strategies used by living systems to tailor peptides into complex natural products but has also allowed to uncover novel RiPP families. In this review, we summarize the current knowledge on radical SAM enzymes catalyzing RiPP post-translational modifications and discuss their mechanisms and growing importance notably in the context of the human microbiota.